Role of extracorporeal shockwave therapy in patients with rotator cuff tendinopathy: synthetic analysis of last two decades - Arooj Fatima; Haider Darain; Syed Amir Gilani; Ashfaq Ahmad; Asif Hanif; Shiza Kazmi (Journal of the Pakistan Medical Association, 2021)
Objective: The study is designed explore the current evidence on effectiveness of shockwave therapy in patients with rotator cuff tendinopathy from 2000-2019. Methodology: Data bases were searched including Cochrane, Medline, Embase and PEDro from 2000 to latest. A thorough search was performed to retrieve articles missed through databases as well as unpublished grey literature. Methodological quality assessment was performed using Cochrane risk of bias tool and included studies were critically appraised using PEDro scale. Results: In current review, 11 articles were finally included based on eligibility criteria. However data was not extractable from 2 studies due to which 9 studies were finally reviewed as shown in figure I. There were 8 Randomized trials and 1 randomized pilot study. The summary of critical appraisal of included studies through PEDro scale was done which showed that 4 studies had high quality and 5 studies fall under the category of fair. Conclusion: Extracorporeal shockwave therapy showed significant improvement in terms of reducing pain and improving functional mobility as compared to traditional rehabilitation in patients with rotator cuff tendinopathy in some studies however in others results were not found to be significant. This systematic review has established that there is no consensus between both interventions however; extracorporeal shockwave therapy is an acceptable practical alternative among patients having tendinopathy. Keywords: Extracorporeal shockwave therapy, Rotator cuff tendinopathy, Systematic review, Continuous...